2018
DOI: 10.1093/mnras/sty789
|View full text |Cite
|
Sign up to set email alerts
|

Instability of supersonic cold streams feeding galaxies–II. Non-linear evolution of surface and body modes of Kelvin–Helmholtz instability

Abstract: As part of our long-term campaign to understand how cold streams feed massive galaxies at high redshift, we study the Kelvin-Helmholtz instability (KHI) of a supersonic, cold, dense gas stream as it penetrates through a hot, dilute circumgalactic medium (CGM). A linear analysis (Paper I) showed that, for realistic conditions, KHI may produce nonlinear perturbations to the stream during infall. Therefore, we proceed here to study the nonlinear stage of KHI, still limited to a two-dimensional slab with no radiat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 85 publications
(168 reference statements)
3
36
0
Order By: Relevance
“…This has motivated idealized studies of cold streams, such as the ones by Mandelker et al (2016), Padnos et al (2018) and Mandelker et al (2019), where instability mechanisms can be more easily understood and the streams can be properly resolved. These studies considered the cold streams using ideal hydrodynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has motivated idealized studies of cold streams, such as the ones by Mandelker et al (2016), Padnos et al (2018) and Mandelker et al (2019), where instability mechanisms can be more easily understood and the streams can be properly resolved. These studies considered the cold streams using ideal hydrodynamics.…”
Section: Resultsmentioning
confidence: 99%
“…The key difference between our models of cold streams and the ones studied by Mandelker et al (2016), Padnos et al (2018) and Mandelker et al (2019) is that we include a magnetic field and treat the system with ideal MHD (see e.g. Freidberg 2014).…”
Section: Idealized Magnetized Cold Stream Modelmentioning
confidence: 99%
“…Examples of large-scale perturbation may be caused by gravitational accretion combined with hydrodynamical (e.g., Kelvin-Helmholtz) or thermal instabilities as we will discuss elsewhere (Vossberg, Cantalupo & Pezzulli, in prep. ; see also Mandelker et al 2016;Padnos et al 2018;Ji et al 2018). Because these density perturbations will be either highly over-pressured or under-pressured for large σ we expect that they would dissipate quickly.…”
Section: Log-normal Density Distributionmentioning
confidence: 97%
“…In such a scenario, the angular momentum segregation between DM and gas could be construed as an artefact of poor numerical resolution in filaments. Several authors (Freundlich et al 2014;Mandelker et al 2016;Padnos et al 2018;Mandelker et al 2019;Berlok & Pfrommer 2019) carried out idealised simulations of filaments entering a halo, and concluded that they should be stable, given their width and velocity. Cornuault et al (2018) used a phenomenological model of a gas stream to explore the possibility of a turbulent, multi-phase filament.…”
Section: Introductionmentioning
confidence: 99%